SCIENTIFIC ARTICLE BIOREMEDIATION OF SOIL CONTAMINATED WITH HEAVY METALS - Meiad Mahdi Al Jaberi (European Journal of Agricultural and Rural Education, 2024)
Soils in many regions of the world are exposed to pollution with toxic heavy metals as a result of human activity in many fields, especially industrial and agricultural practices, as well as the use of agricultural pesticides and phosphate fertilizers in terms of manufacturing, mining, or disposal of their waste. Human activity in disposing of wastewater and factories waste and their use for agricultural purposes greatly contributes to this problem of pollution when contaminated soil is used to produce food by growing various crops, since it is easy for these elements to enter the food chain when eating these crops, which increases the risks to human health